Isolation and biosynthesis of daturamycins from Streptomyces sp. KIB-H1544 - Chen, Yin; Ren, Jinqiu; Yang, Ruimin; Li, Jie; Huang, Sheng-Xiong; Yan, Yijun (Beilstein Journal of Organic Chemistry, 2022)
Two novel diarylcyclopentenones daturamycin A and B (1 and 2), and one new p-terphenyl daturamycin C (3), along with three known congeners (4–6), were isolated from a rhizosphere soil-derived Streptomyces sp. KIB-H1544. The structures of new compounds were elucidated via a joint use of spectroscopic analyses and single-crystal X-ray diffractions. Compounds 1 and 2 belong to a rare class of tricyclic 6/5/6 diarylcyclopentenones, and compounds 3–6 possess a C-18 tricyclic aromatic skeleton. The biosynthetic gene cluster of daturamycins was identified through gene knockout and biochemical characterization experiments and the biosynthetic pathway of daturamycins was proposed.
Keywords: biosynthesis; diarylcyclopentenone; polyporic acid synthetase; p-terphenyl; Streptomyces